[tsélem] צלם na Bíblia Hebraica: contribuições para um novo dicionário semântico do hebraico bíblico - Grimm, Charles Ludwig (2012)
This research is a complete mapping of occurrences of צלם [tsélem] in the Hebrew Bible seeking to bring contributions to the production of articles in the Semantic Dictionary of Biblical Hebrew . This study fits into a larger project devoted to an in depth study of a biblical Hebrew lexeme.